Effects of a 24-h naproxen dose on hydration and electrolyte measures during moderate-intensity cycling in the heat - Dawn M. Emerson; Toni M. Torres-McGehee; J. Mark Davis; Stephen C.L. Chen; J. Larry Durstine; Craig E. Pfeifer; Charles C. Emerson; Justin V. Stone; Joseph D. Bivona (Canadian Science Publishing, 2017)
Few controlled laboratory studies have examined the negative effects non-steroidal anti-inflammatory drugs can have on fluid-electrolyte balance during exercise. Our objective was to determine whether a 24-h naproxen dose negatively affected hydration and electrolyte measures before, during, and 3 h after 90 min of cycling in a hot or ambient environment. Using a double blind, randomized and counterbalanced cross-over design, 11 volunteers (six male, five female) completed four trials, with conditions as follows: (1) placebo and ambient, (2) placebo and heat, (3) naproxen and ambient, and (4) naproxen and heat. We found no statistically significant differences among experimental conditions for any dependent measures. Though not statistically significant, mean fluid volume was higher and urine volume was lower during naproxen trials compared with placebos. Mean aggregate plasma sodium was <135 mmol/L at all time points and did not significantly change over time. Overall plasma potassium significantly increased pre- (3.9 ± 0.4) to post-exercise (4.2 ± 0.4 mmol/L, p = 0.02). In conclusion, an acute naproxen dose did not significantly alter hydration-electrolyte balance. The trend for naproxen to increase fluid volume and decrease urine volume suggests the start of fluid retention, which should concern individuals at risk for hyponatremia or with pre-existing cardiovascular conditions.